Pengembangan Alat Musschenbroek dan Panduan Praktikumnya untuk Membangun Inkuiri Siswa - Fathin Irina Diatri (JURNAL EKSAKTA PENDIDIKAN (JEP), 2020)
This developmental research aims to produce Musschenbroek's apparatus with practice’s guidance that not only can be utilized to determine compare coefficient effervesces length an object but can also be utilized to account coefficient point effervesces length and build inquiry’s student. Development that doing based on ADDIE'S model. Procedure of this research and development is consisting of five phases, which is analysis, design, development, implementation, and evaluation. Result of this development is acquired Musschenbroek's apparatus that can applicable to account coefficient point effervesces length and practice’s guidance that can build inquiry’s student. Musschenbroek's apparatus that designing is interesting, easy, and very helpful for student bases on the result of field test. Developed practice’s guidance have also interesting, easy, and helpful. Practice's guidance load learning steps that corresponding to build inquiry’s student with pretty good category, which is on aspect makes hypothesis, collecting data, testing hypothesis, and formulates conclusion. Learning used Musschenbroek's apparatus and practice’s guidance effective to increase student learning result with category moderate (n-gain = 0,57).